Transparency and sustainability of budgetary policy in the new EU member states: Executive summary - Friedrich Heinemann; Michael Knogler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
The principles of budgetary completeness and transparency are indispensable elements of fiscal surveillance in the European Union. Within this context, this study deals with the leading question to which extent budgetary policy in the ten new EU member states (NMS) can be regarded as transparent and sustainable. A variety of institutional and quantitative methods (among others analyses of fiscal forecast quality, stock flow adjustments, consolidation structure and a simulation of the EU budgetary system) is applied. In the assessment of current budgetary trends, the employed criteria consistently underline the fact that the Baltic countries and Slovenia find themselves in a relatively stable fiscal situation. In contrast to that, Hungary ranks low on the scale with its chronic deficits, its poor record for sticking to consolidation announcements and an unfavourable consolidation structure.
Keywords: 330; Public Budget; EU Membership; Baltic States; Slovenia; Hungary; Öffentlicher Haushalt; EU-Mitgliedschaft; Baltische Staaten; Slowenien; Ungarn